SERIES: APPLIED BUSINESS PROCESS ENGINEERING (Part 8) COSTING MODELS APPLIED TO SET IN MANUFACTURING - Porlles Loarte, José Angel (2007)
In the industry every time more is generalized the manufacture of varied products of simultaneous way with similar values, denominated joint products from the same raw material and/or process of manufacture, giving rise to the joint cost. Then the Engineer of Processes faces the necessity to calculate the costs of these individual products, task that often is a cornplex subject since the joint costs are not specifically identifiable with some of the products that are making in simultaneous form. The intention of this eighth part is to provide the excellent models, methodology and criteria of how it must assign the joint costs to each joint product.